2002
DOI: 10.1038/sj.bjc.6600660
|View full text |Cite
|
Sign up to set email alerts
|

Block sequential adriamycin CMF – optimal non-myeloablative chemotherapy for high risk adjuvant breast cancer?

Abstract: After the publication of the 10-year survival data from Milan on the adjuvant use of the block sequential regimen consisting of four cycles of adriamycin followed by eight cycles of intravenous CMF, many centres adopted this as standard of care for high risk, multiple node-positive breast cancer. For this reason it was identified as the standard arm for the Anglo-Celtic adjuvant high-dose chemotherapy trial. This study reports on the experience of this regimen in 329 women with early breast cancer involving at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…It was noted in that study that there was a strong tendency for the older patients to be undertreated, and in a subsequent study from the same group, looking at alternating CMF and adriamycin, it is clear that older women had a poorer outcome than younger women on the same regimen (Bonadonna et al, 1995b). Interestingly, in a recent audit of over 300 patients treated with that same adriamycin-CMF regimen in 11 centres in UK, Ireland and New Zealand, there was no difference in outcome for older patients (Cameron et al, 2002). These data, together with the observation from the meta-analysis that the benefit of adjuvant chemotherapy appears to diminish with increasing age, led us to hypothesise that it may be a failure to deliver drug dose and/or dose intensity in the older adjuvant breast cancer patient that results in its apparent reduced efficacy.…”
mentioning
confidence: 98%
“…It was noted in that study that there was a strong tendency for the older patients to be undertreated, and in a subsequent study from the same group, looking at alternating CMF and adriamycin, it is clear that older women had a poorer outcome than younger women on the same regimen (Bonadonna et al, 1995b). Interestingly, in a recent audit of over 300 patients treated with that same adriamycin-CMF regimen in 11 centres in UK, Ireland and New Zealand, there was no difference in outcome for older patients (Cameron et al, 2002). These data, together with the observation from the meta-analysis that the benefit of adjuvant chemotherapy appears to diminish with increasing age, led us to hypothesise that it may be a failure to deliver drug dose and/or dose intensity in the older adjuvant breast cancer patient that results in its apparent reduced efficacy.…”
mentioning
confidence: 98%
“…Regulation and disturbance of the cancer cell cycle is a therapeutic target for development of new anticancer drugs. [ 14 ] Apoptosis has been defined as counterbalance for cell proliferation in maintaining normal tissue homeostasis. [ 15 ] In this study, it could be found that n-butyl-β-D-fructofuranoside was likely to suppress the Bel-7402 cells not only by interfering the cell cycle but also by inducing apoptosis.…”
Section: Discussionmentioning
confidence: 99%